2011
DOI: 10.1152/jn.00120.2011
|View full text |Cite
|
Sign up to set email alerts
|

Activity of motor cortex neurons during backward locomotion

Abstract: Cell-or network-driven oscillators underlie motor rhythmicity. The identity of C. elegans oscillators remains unknown. Through cell ablation, electrophysiology, and calcium imaging, we show: (1) forward and backward locomotion is driven by different oscillators; (2) the cholinergic and excitatory A-class motor neurons exhibit intrinsic and oscillatory activity that is sufficient to drive backward locomotion in the absence of premotor interneurons; (3) the UNC-2 P/ Q/N high-voltage-activated calcium current und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…The right and left limbs were stepping in anti-phase. These characteristics of backward locomotor pattern were similar to those described earlier for intact (Buford and Smith, 1990; Buford et al, 1990; Zelenin et al, 2011) and decerebrate cats (Musienko et al, 2007). …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The right and left limbs were stepping in anti-phase. These characteristics of backward locomotor pattern were similar to those described earlier for intact (Buford and Smith, 1990; Buford et al, 1990; Zelenin et al, 2011) and decerebrate cats (Musienko et al, 2007). …”
Section: Resultssupporting
confidence: 87%
“…Most bipeds and quadrupeds, in addition to the main form of locomotion – forward walking, are also capable of backward and sideward walking (e.g. Stein et al, 1986; Buford and Smith, 1990; Buford et al, 1990; Rossignol, 1996; Deliagina et al, 1997; Zelenin et al, 2011). Also, the steps deviated from the direction of progression are used for correcting perturbations of balance during forward walking (Karayannidou et al, 2009; Musienko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant differences between the two sequences in the location of the most active voxel within the primary motor hand area contralateral to the performing hand or in the mean magnitude of activity evoked during the performance. The current results, therefore, are in line with the results of animal studies showing that the representation of motor sequences in M1 may not be reliably assessed by averaging neuronal activity (Zelenin et al, 2011;Ben-Shaul et al, 2004;Hatsopoulos, Paninski, & Donoghue, 2003). There are data suggesting that different tasks can be reliably expressed in the modulation patterns rather than in the population mean of activity of motor cortex neurons (Zelenin et al, 2011), presumably reflecting the fact that the same neuronal pool in the motor cortex can be recruited in different tasks ( Yang et al, 2014;Zelenin et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…How the different commands are channeled to spinal cord networks remains poorly understood. In a few previous studies, the activity of forelimb-and hindlimb-related PTNs were compared and it was found that while some quantitative differences exist, qualitatively, commands sent by PTNs to forelimbs and hindlimbs are quite similar (Karayannidou et al 2009;Widajewicz et al 1994;Zelenin et al 2011). In this study we hypothesized that there are different spinal targets within each girdle's neuronal network that receive different signals from the motor cortex during locomotion.…”
mentioning
confidence: 81%